2008
DOI: 10.1111/j.1467-8721.2008.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Episodic Memory

Abstract: Research shows sex differences in episodic memory. These differences vary in magnitude as a function of the type of material to be remembered. Throughout the life span, verbal episodic-memory tasks yield differences favoring women. In contrast, episodic-memory tasks requiring visuospatial processing result in differences favoring men. There are also sex differences favoring women on episodic-memory tasks requiring both verbal and visuospatial processing and on face-recognition tasks. Thus, there may be a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
172
5
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(205 citation statements)
references
References 18 publications
25
172
5
3
Order By: Relevance
“…Previous studies with young and older adults suggested a benefit for women in verbal episodic memory, as well as a comparable benefit for men in the visuospatial domain (see Herlitz, Airaksinen, & Nordstrom, 1999;Herlitz, Nilsson, & Backman, 1997;Herlitz & Rehnman, 2008;Lewin et al 2001). The memory benefit for verbal materials observed in women over men was confirmed in a study by Herlitz and Yonker (2002), who tested young adult men and women in a series of tasks involving the recall and recognition of verbal material, faces, and abstract pictorial stimuli.…”
Section: Gender Differences In Episodic Memorymentioning
confidence: 53%
See 1 more Smart Citation
“…Previous studies with young and older adults suggested a benefit for women in verbal episodic memory, as well as a comparable benefit for men in the visuospatial domain (see Herlitz, Airaksinen, & Nordstrom, 1999;Herlitz, Nilsson, & Backman, 1997;Herlitz & Rehnman, 2008;Lewin et al 2001). The memory benefit for verbal materials observed in women over men was confirmed in a study by Herlitz and Yonker (2002), who tested young adult men and women in a series of tasks involving the recall and recognition of verbal material, faces, and abstract pictorial stimuli.…”
Section: Gender Differences In Episodic Memorymentioning
confidence: 53%
“…Past literature had indicated that women have superior verbal memory ability as compared with men (e.g., Herlitz & Rehnman, 2008;Meinz & Salthouse, 1998), as well as that males suffer a larger age-related decline in tasks requiring binding (e.g., Maylor et al, 2007), but these differences had not been tested with respect to the AD of older adults. Thus, the AD may be due to a decline in the associative memory of men relative to women.…”
Section: Gender Differences In Episodic Memorymentioning
confidence: 99%
“…Igualmente, también obtienen una puntuación superior en plasticidad cognitiva evaluada a partir de la puntuación de ganancia en la prueba AVLT-PA. Estos resultados confirman la hipótesis de que las mujeres en la vejez muestran un rendimiento superior a los hombres en tareas de memoria de tipo verbal (Aarsten, Martin y Zimprich, 2004;Herlitz y Rehnman, 2008). No obstante, estudios previos hacían prever un mejor rendimiento en fluidez verbal en las mujeres (Gerstorf et al, 2006).…”
Section: Discussionunclassified
“…They proposed that in comparison to the digit-span performance, LNS performance showed a greater decline with increased age, probably due to a greater deterioration in executive functioning that underlies LNS performance. In terms of gender differences, a female advantage in episodic memory retrieval is predominantly reported (e.g., Geffen, Moar, O'Hanlon, Clark, & Geffen, 1990;Herlitz, Nilsson, & Bäckman, 1997;Herlitz & Rehnman, 2008;Hultsch, Masson, & Small, 1991). However, there are mixed findings about the presence of gender differences in WM (Loring-Meier & Halpern, 1999;Lynn & Irwing, 2008;Schmidt et al, 2009).…”
mentioning
confidence: 91%